ANALISIS KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN BURU SELATAN - Suparman, Suparman (Patria Artha University, 2021)
This study aims to analyze the performance of the Regional Disaster Management Agency of South Buru Regency, as well as to find out the factors that can hinder and support the improvement of the performance of the Regional Disaster Management Agency of South Buru Regency. This research is descriptive using a qualitative approach so that to support this research activity, data collection from informants was carried out. Data analysis is preceded by collecting and collecting data or information in the field, after which it is classified according to the type and group, then the analysis is carried out or interpreted qualitatively. Based on the results of the analysis, it is known that the performance of the Regional Disaster Management Agency (BPBD) of South Buru Regency. The performance of the Regional Disaster Management Agency (BPBD) of South Buru Regency is good but not optimal. The Supporting Factors for the Performance of the Regional Disaster Management Agency (BPBD) of South Buru Regency, namely an organizational culture that is running well, while the inhibiting factor is the lack of rewards in the form of bonuses for employee performance, lack of personnel, quality of human resources that are still lacking, still limited availability of facilities and infrastructure, as well as difficulties in reaching the affected areas to carry out disaster management due to the geographical conditions of the affected areas.